Homeless management information system customization intervention. - Fitch D (Journal of Human Behavior in the Social Environment, 2010)
Homeless management information systems (HMISs) are being implemented nationwide in response to a Congressional mandate to understand the phenomenon of homelessness. Though federal dollars have been provided to implement these systems and though HMISs have been developed by private vendors to meet this mandate, most shelters are not utilizing these systems fully. A case study was undertaken to understand why that was happening in one shelter. Using a cybernetic system analysis revealed the information flows in the agency, thereby allowing me to customize the HMIS, making it more likely to be used for daily shelter operations.